GENDER DIFFERENCES IN DEPRESSIVE SYMPTOMS AMONG MEXICAN ADOLESCENTS - Masten, William G.; Cadwell-Colbert, A. Toy; Williams, Velma; Jerome, Wanda W.; Mosby, Laura; Barrios, Yolanda; Helton, Joseph (Anales de Psicología / Annals of Psychology, 2003)
Existing research on gender differences in depressive symptoms among Mexican adolescents is limited to studies conducted in Mexico City. The purpose of this study was to continue the investigation of gender and depression among male and female adolescents living in Mexico. The results of the scores of two groups of adolescents that participated in the study indicated no significant gender differences on depression as measured by the Spanish version of the Center for Epidemiological Studies Depression Scale (CES-D). These findings contradicted all but one previous study of gender differences in adolescent depression -research which studied adolescents living in “developed” versus “developing” countries. Several alternative explanations, including how the effect of living in a rapidly developing country, such as Mexico, might be impacting gender and depression in Mexican adolescents, were explored. In addition, stress, acculturation, sex-typed personality characteristics, and suicidal ideation were discussed. Additional research into the relationship between gender and depression among adolescents living in Mexico was recommended.